Whole body biomechanical burden of healthcare workers: proposal for a complementary risk assessment and management tool (HOARA) - Baracco, Alessandro; Coggiola, Maurizio; Bosio, Davide; Perrelli, Ferruccio; Garzaro, Giacomo; Turcu, Veronica; Pira, Enrico (La Medicina del Lavoro, 2019)
Introduction: We have developed a new tool, named Holistic Approach Risk Assessment (HOARA), to support occupational safety and health professionals (OSH) in risk assessment and management when evaluating the biomechanical load of healthcare workers. Objectives: The primary aim of the HOARA is to support OSH in risk assessment and management of biomechanical hazards in healthcare facilities. This tool ensures a superior level of analysis by targeting independently various body compartments during all activities completed throughout the work shift. These include: head, neck, back and upper and lower limbs. Methods: For each body segment, ergonomic determinants were defined on the basis of previous literature, according to which task and job analyses were performed. Upon direct observation, ergonomic factors were given a score based on their temporal extent. Subsequently, action-body segment raw indices and weighted indices were calculated. Results: Results of the application of the method are shown. Of note, a relational database was set up to improve its usability. Conclusions: From an occupational health perspective, the HOARA, integrated with other methods, is expected to allow a more effective management of human resources, especially when assigning workers to specific jobs or tasks. Overall, the HOARA will be instrumental in assessing the impact of fitness for work judgments on work organization and its resources, in compliance with the guidelines from the Società Italiana di Medicina del Lavoro (SIML).